Pacing strategy and V·O2 kinetics during a 1500-m race - Hanon, C.; Leveque, J. M.; Thomas, C.; Vivier, L. (International Journal of Sports Medicine, 2008)
We investigated the oxygen uptake response (V·O2) to a 1500-m test conducted using a competition race strategy. On an outdoor track, eleven middle-distance runners performed a test to determine V·O2max, velocity associated with V·O2max (v-V·O2max) and a supramaximal 1500-m running test (each test at least two days apart). V·O2max response was measured with the use of a miniaturised telemetric gas exchange system (Cosmed, K4, Roma, Italy). The 1500-m running test was performed at a mean velocity of 107. 6 + 2 % v-V·O2max. The maximal value of oxygen uptake recorded during the 1500-m test (V·O2peak) was reached by subjects at 75.9 + 7.5 s (mean + SD) (i.e., 459 ± 59 m). The time to reach V·O2max (TV·O2peak) and the start velocity (200- to 400-m after the onset of the 1500 m) expressed in % v-V·O2max were negatively and significantly correlated (p < 0.05), but our results indicate that a fast start does not necessarily induce a good performance. These results suggest that V·O2max is reached by all the subjects at the onset of a simulated 1500-m running event and are therefore in contrast with previous results obtained during treadmill running.